2020
DOI: 10.1111/jse.12690
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of phylogenetic relatedness and trait selection on the elevational distribution of Rhododendron species

Abstract: Congeneric species may coexist at fine spatial scales through niche differentiation, however, the magnitude to which the effects of functional traits and phylogenetic relatedness contribute to their distribution along elevational gradients remains understudied. To test the hypothesis that trait and elevational range overlap can affect local speciesʼ coexistence, we first compared phylogenetic relatedness and trait (including morphological traits and leaf elements) divergence among closely related species of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…A common pattern across previous studies and ours is that at higher elevations, alpine species of Rhododendron tend to be more synchronized in their flowering (Hart & Salick, 2018) and more similar in morphology, for example, have smaller leaves (Zou et al, 2021). These patterns likely reflect the shorter flowering season and environmental filtering of harsher alpine climates.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A common pattern across previous studies and ours is that at higher elevations, alpine species of Rhododendron tend to be more synchronized in their flowering (Hart & Salick, 2018) and more similar in morphology, for example, have smaller leaves (Zou et al, 2021). These patterns likely reflect the shorter flowering season and environmental filtering of harsher alpine climates.…”
Section: Discussionsupporting
confidence: 78%
“…Studies of Rhododendron co‐occurrence in relation to phenology, traits and relatedness have been carried out at sites elsewhere in the Hengduan Mountains (Hart & Salick, 2018; Zou et al, 2021) and the eastern Himalaya (Basnett et al, 2021; Basnett, Ganesan, et al, 2019; Basnett, Nagaraju, et al, 2019). While the methods of these studies varied and differed from ours, some pertinent comparisons can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Rhododendron is one of the most taxonomically difficult and speciesrich groups for species identification and phylogenetic inference due to its complex evolutionary history (Yan et al, 2015). Numerous species of Rhododendron occur sympatrically and undergo extensive interspecific hybridization and/or introgression (Ma et al, 2010;Milne et al, 2010;Yan et al, 2017Yan et al, , 2019Zou et al, 2020). Hybridization/ introgression can result in the sharing of maternally inherited plastid genomes between closely related species (Du et al, 2009), and thus the plastid genome may not track species boundaries (Hollingsworth et al, 2016;Petit & Excoffier, 2009).…”
Section: Potential Reasons For Species Discrimination Failure In Rhod...mentioning
confidence: 99%
“…Therefore, monsoon duration seems to be a major factor in determining the distribution limit of this species. In the third paper, Zou et al (2021) explored the relationship between functional traits and phylogenetic relatedness along altitudinal distributions of the Rhododendron species. They found that closely related species had high trait similarity.…”
Section: Ecological Adaptationmentioning
confidence: 99%